Absence of frontal sinus in Turkish individuals - Aydmlioglu, A; Kavakli, A; Erdem, S (Yonsei Univ Coll Medicine, 2003)
The frontal sinus has been used for personal identification since the early part of the 20th century as a result of its tremendous interindividual variation. The frontal sinus is present in approximately 90% of adults. However, some populations have a higher proportion of people without a frontal sinus. This study investigated the frequency of the absence of frontal sinuses in Turkish individuals. The present study was performed retrospectively on the CT scans of the paranasal sinuses in the axial and coronal planes from a series of 1200 cases. A bilateral absence and a unilateral absence of sinuses were found in 3.8% and 4.8% of cases, respectively. The clinical significance of the frontal sinuses and their absence are also discussed.
Keywords: frontal sinus; aplasia; personal identification; CT